Obtenção de nanocristais de celulose a partir do resíduo da produção de etanol do bagaço de cana-deaçúcar pela rota enzimática - Camargo, Lais Angelice de (Universidade Federal de São Carlos, 2015)
This study addressed the use of solid residues from the process of cellulosic ethanol production using the enzymatic hydrolysis of sugarcane bagasse for the production of cellulose nanocrystals (CNCs). Bagasse submitted to two types of pretreatments (steam explosion - SESB and hydrothermal - HSB) was hydrolyzed with two different enzymatic loads using a commercial enzymatic extract. The solid residues generated after the hydrolysis were purified with NaOH 5% (w/w) at 55 °C and H2O2 35% (v/v) followed by an acid hydrolysis at 45 °C with H2SO4 60% (w/w) and extraction of 30 min in order to obtain the CNCs. The samples of SESB and HSB presented cellulose contents of 61 and 54%, respectively. The conversion in the enzymatic hydrolysis step ranged from 25 to 55% for SESB and 33 to 59% for HSB, along with the increase of enzymatic loading. And besides the release of glucose into the liquid phase, it was also generated solid residues with significant quantity of cellulose to be used for CNCs production. Due to decreasing of the cellulose crystallinity indexes (CI%) of the residual solid, a purification procedure was necessary, which raised the CI by about 30% for SESB residues and approximately 25% for HSB residues. The resulting CNCs presented proper physical and chemical characteristics, such as degradation temperature exceeding 230°C and crystallinity around 79% for both matrices. The CNCs obtained feature of needle with length between 193 and 246 nm and diameter of between 17 and 30 nm. These results indicate that CNCs produced from the residual streams of enzymatic route of cellulosic ethanol production from the sugarcane bagasse have the characteristics suitable for this type of product. Therefore, the use of these solids residues for new materials production, such as NCCs for use in different applications proved to be potentially promising for adding value to the bioenergy sector.
OBTAINING CELLULOSE NANOCRYSTALS FROM THE RESIDUE OF ETHANOL PRODUCTION FROM SUGARCANE BAGASSE BY ENZYMATIC ROUTE
Keywords: Obtenção de nanocristais de celulose; Bagaço de cana-de-açúcar; Resíduo da produção de Etanol 2G; Reaproveitamento de resíduo; Hidrólise enzimática; CIENCIAS EXATAS E DA TERRA::QUIMICA